PENGEMBANGAN HARD SKILL BERBASIS ECOPRINT DAN MERONCE DI TERAS MERICA TANGERANG SELATAN - Marlia Retno Wulan; Faizah Hanum; Ariyani Yeri Pranata; Indah Rama Fidia; Irfa Erfiyana; Yulia Putri Cahya Ningrum; Firdha Nadya Putri; Khusniatun Aisyah; Putri Anggun Dita; Rinda Puspita (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This community service activity aims to develop practical skills (hard skills) and creativity of children in the Teras Merica environment, South Tangerang. The activity is carried out through four main stages: preparation, implementation, mentoring, and evaluation. The target of the activity was 16 children aged 10-11 years who lived around Jalan Merica, Pondok Cabe, South Tangerang. The results of the activity showed a significant improvement in aspects of children's technical skills, creativity, confidence, and collaboration skills. The products produced are ecoprints on fabrics and totebags as well as meronce products in the form of bracelets, rings, and keychains. This activity is proof that skills-based learning can be an effective means of developing children's potential and forming awareness of the economic value of artworks. It is hoped that similar activities can be developed in a sustainable manner by involving the participation of the community and surrounding educational institutions.